Adaptation of North Atlantic Albacore Fishery to Climate Change: Yet Another Potential Benefit of Harvest Control Rules - Merino, Gorka; Arrizabalaga, Haritz; Arregui, Igor; Santiago, Josu; Murua, Hilario; Urtizberea, Agurtzane; Andonegi, Eider; De Bruyn, Paul; Kell, Laurence T. (Frontiers in Marine Science, 2019)
Fisheries are constrained by ecosystem productivity and management effectiveness. Climate change is already producing impacts on marine ecosystems through overall changes in habitats, productivity and increased variability of environmental conditions. The way how these will affect fisheries is under debate and, also is the best course of actions to face this global challenge. harvest control rules are sets of pre-agreed rules that can be used to determine catch limits periodically and describe how harvest is automatically controlled by management in relation to the state of some indicator of stock status. In 2017, the International Commission for the Conservation of Atlantic Tunas adopted a harvest control rule for North Atlantic albacore. This harvest control rule was evaluated using Management Strategy Evaluation against the main sources of uncertainty inherent to this fishery. Here, we use the same framework to evaluate the robustness of the adopted rule against two types of potential climate change impacts on North Atlantic albacore dynamics. First, we evaluate how the control rule would perform in the event of overall changes in productivity in the North Atlantic and second, against increases in climate driven recruitment variability. Overall, our results suggest that the adopted harvest control rule is robust to these climate driven impacts and also suggests bounds at which the current management framework would be vulnerable to climate change. Throughout the manuscript we also discuss the potential of harvest control rules and harvest strategies to adapt fisheries management to a changing environment. Our main conclusion is that despite the many uncertainties on climate impacts on fisheries, efficient fisheries management will be critical to ensure the sustainability of fisheries in the future.